Hydrogeochemical characteristics and evaluation of groundwater resources of Jilin Province, China - Zeng, Zhaojun; Cui, Yueju; Zhou, Xiaocheng; Pan, Xiaodong; Sun, Fengxia; Liu, Yinan; Tian, Jiao; He, Miao; Zhang, Yongxian; Yan, Yucong; Zou, Zhenyu; Wang, Yuwen; et al. (Frontiers in Water, 2023)
Understanding the hydrogeochemical characteristics is essential for effective water resource management. A total of 64 groundwater samples were collected from 32 monitoring wells in Jilin Province, China, in two sets of data.Measurements were conducted to assess hydrogeochemical processes and groundwater quality, including the determination of hydrogeochemical parameters, conventional ions, trace elements, and stable isotopes (δD and δ 18 O). The results indicate that the groundwater is slightly alkaline, with major cations including Na + , Ca 2+ , Mg 2+ , and K + , and dominant anions of HCO3 -, Cl -, and SO4 2-. Most of the groundwater samples belong to the Ca-HCO3 and Na-HCO3 types, formed by mineral dissolution of calcite, dolomite, gypsum, silicates, and carbonates. Stable isotope analysis reveals that groundwater recharge in Jilin primarily comes from atmospheric precipitation between elevations of 1430 to 2348m. Strong correlations among trace elements suggest a common source. The majority of groundwater in the study area is classified as Class I to Class III on the Water Quality Index (WQI), with Hazard Quotient (HQ) and Hazard Index (HI) values below 1. This indicates excellent water quality and minimal health risks associated with human consumption. Notably, trace elements are enriched in the TanLu fault zone. Thus, this study provides scientific guidance for the utilization and allocation of groundwater resources in Jilin Province.